MARTABAT MANUSIA DI ERA MESIN: TANTANGAN ETIKA DALAM PERKEMBANGAN TEKNOLOGI ARTIFICIAL INTELLIGENCE - Gerardus B Duka; Gregorio A. M. Kanaf; Rosadalima Lema Bao (Pastoralia, 2026)
The development of Artificial Intelligence (AI) technology has brought significant changes to various aspects of human life, ranging from education, economy, and healthcare to digital communication. While these advancements offer convenience and efficiency in daily activities, they also pose challenges to human values and dignity. This journal aims to analyze the impact of AI development on human life and examine the importance of digital ethics in preserving human values in the machine age. The method employed is a literature review, gathering various sources from books, scientific journals, and articles related to AI technology and digital ethics. The discussion reveals that the utilization of AI without ethical oversight can trigger various issues, such as diminished social interaction, misuse of personal data, algorithmic bias, and human dependency on technology. Therefore, moral awareness, regulation, and digital ethics education are essential to ensure that technological developments remain oriented toward human well-being. In conclusion, AI should serve as a tool that assists humans, rather than replacing human values and individual dignity in social life